The rise and fall of the Third Reich : - Shirer, William L. (Simon and Schuster, 1960)
Since its publication in 1960, William L. Shirer's monumental study of Hitler's German Empire has been widely acclaimed as the definitive record of this century's blackest hours. The Rise and Fall of the Third Reich offers an unparalleled and thrillingly told examination of how Adolf Hitler nearly succeeded in conquering the world. With millions of copies in print around the globe, it has attained the status of a vital and enduring classic.